The effect of feeding cassava root meal on the performance, carcass characteristics, serum and urinary thiocyanate concentration of fryer rabbits - ESHIETT, N. O.; OMOLE , T. A.; ADEMOSUN, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Thirty-two, five weeks old New Zealand White fryer rabbits were fed four diets containing 0, 15, 30 or 45% cassava root meal (CRM) in an experiment designed to investigate the utilization of CRM by fryer rabbits. The levels of CRM fed did not adversely affect the growth rate of the rabbits, but those fed 0 and 15% CRM diets consumed significantly less (P<0.05) feed than those on the 45% CRM diets. Similarly, rabbits fed the control (0% CRM) diet utilized their feed better (P< 0.05) than those on the CRM diets. The 15 and 30% CRM diets were utilized similarly but were superior to the 45% CRM. The serum thiocyanate concentration of rabbit fed the 0, 15, 30 and 45% CRM diets were 1.59, 1.72, 1.66 and 1.76mg/100ml respectively. Corresponding values for urine thiocyanate were 2.94, 3.15, 3.15 and 3.21mg/100ml. These values were however not significantly different. Carcass quality was similar across treatments.